The size effect in mechanical properties of boron nitride nanotube under tension - Danh Truong, Nguyen (Vietnam Journal of Science and Technology, 2017)
This work aimed at investigating the mechanicals properties of boron nitride nanotubes (BN-NTs) under uniaxial tension using atomic finite element method with Tersoff potential. The zigzag and armchair nanotubes with different length and diameter are considered for researching effect on mechanicals behavior of BN-NTs. It is found that Young’s modulus of BN-NTs are independent of the tubular length, but slightly increase when the diameter go rise. At the given strain, axial stress in the armchair tubes is higher than that in the zigzag ones.